Faktor Perilaku Penggunaan Vape pada Remaja dan Implikasinya terhadap Bimbingan dan Konseling - Shelfa Ramadhani; Rici Kardo; Rahmawati Wae (Kartika: Jurnal Studi Keislaman, 2026)
This research is motivated by the increasing use of e-cigarettes (vapes) which has become a trend among adolescents. This study aims to describe the behavior of vape use in adolescents from cognitive, emotional, social, and behavioral factors. This study uses a qualitative descriptive approach involving two key informants and three additional informants. Data was collected through interviews and observations, then analyzed using data reduction techniques, data presentation, and conclusion drawn. The results of the study show that cognitive factors are characterized by adolescents' limited knowledge of vaping so that they consider vaping to be more modern and safer than conventional cigarettes. Emotional factors indicate that vapes are used to cope with stress, boredom, and stress and provide a sense of comfort. Social factors show the influence of peers, family, and social norms on vaping use behavior. Meanwhile, behavioral patterns show that vape use is carried out repeatedly until it becomes a routine that is difficult to reduce. This study recommends the use of educational videos as a medium of guidance and counseling to increase adolescents' understanding of the dangers of vaping and help reduce its use behavior